Fundamentals of Entrepreneurship (ENT300) : Case study Y.K.L and Y Enterprise / Sharon Livan Ujang ... [et al.] - Ujang, Sharon Livan; Jerry, Jane Effarenda; James, Vivian Urai; Samshulhana, Muhamad Syafiq (2019)
Y.K.L. AND Y ENTREPRISE have been recognized by all UITM Campus Samarahan and UNIMAS students. This is because the enterprise are located in Desa Ilmu Kota Samarahan which is student's centre. The services that offered by Y.K.L AND Y ENTERPRISE includes sublimation lanyard, sublimation t-shirt, souvenirs,trophies,plaques,medal,cap,premium gift, embroidery, banner , bunting , digital printing, corporate shirt, t-shirt,and sticker.